Assessment of middle cerebral artery diameter during hypocapnia and hypercapnia in humans using ultra-high-field MRI - Verbree, Jasper; Bronzwaer, Anne-Sophie G T; Ghariq, Eidrees; Versluis, Maarten J; Daemen, Mat J A P; van Buchem, Mark A; Dahan, Albert; van Lieshout, Johannes J; van Osch, Matthias J P (Journal of applied physiology (1985), 2014)
In the evaluation of cerebrovascular CO2 reactivity measurements, it is often assumed that the diameter of the large intracranial arteries insonated by transcranial Doppler remains unaffected by changes in arterial CO2 partial pressure. However, the strong cerebral vasodilatory capacity of CO2 challenges this assumption, suggesting that there should be some changes in diameter, even if very small. Data from previous studies on effects of CO2 on cerebral artery diameter [middle cerebral artery (MCA)] have been inconsistent. In this study, we examined 10 healthy subjects (5 women, 5 men, age 21-30 yr). High-resolution (0.2 mm in-plane) MRI scans at 7 Tesla were used for direct observation of the MCA diameter during hypocapnia, -1 kPa (-7.5 mmHg), normocapnia, 0 kPa (0 mmHg), and two levels of hypercapnia, +1 and +2 kPa (7.5 and 15 mmHg), with respect to baseline. The vessel lumen was manually delineated by two independent observers. The results showed that the MCA diameter increased by 6.8 ± 2.9% in response to 2 kPa end-tidal P(CO2) (PET(CO2)) above baseline. However, no significant changes in diameter were observed at the -1 kPa (-1.2 ± 2.4%), and +1 kPa (+1.4 ± 3.2%) levels relative to normocapnia. The nonlinear response of the MCA diameter to CO2 was fitted as a continuous calibration curve. Cerebral blood flow changes measured by transcranial Doppler could be corrected by this calibration curve using concomitant PET(CO2) measurements. In conclusion, the MCA diameter remains constant during small deviations of the PET(CO2) from normocapnia, but increases at higher PET(CO2) values.